Disciplining the risky subject: a discourse analysis of the concept of resilience in social work literature - Park, Yoosun; Crath, Rory; Jeffery, Donna (Journal of social work : JSW, 2020)
Summary The concept of resilience has become an established, taken-for-granted concept in social work. This poststructuralist discourse analysis of randomly sampled social work articles on resilience examines the discursive mechanisms through which the concept of resilience has been constructed in particular ways and considers the political effects of such usage. Findings The study of resilience is always a post facto analysis; markers of resilience are predetermined by dominant ideas of the normal and the normative subject. Systemic risk factors such as poverty and inequality are acknowledged to be productive of subjects in need of resilience. Yet, those structures are relegated to the margins of the manuscript and elided in favor of individualized analysis and intervention; the identified locus of risk and the targeted site of interventions are entirely at odds. Resilience, thus, serves as a designation for risky subjects’ capacity to accommodate—not actively change—their social/political environments, including their interactions with social work and social workers. It functions as a technology of the neoliberal self that allows social workers to construct and manage subjects capable of self-management and productive self-sufficiency. Application The resilience enterprise thus short-circuits social work’s aims for social justice. Examination of the discourse of resilience for their implications for practice, education, and research is a political imperative for social work and is necessary to open up new sightlines of possibility for a reenergized, more complex social work praxis. Suggestions for future directions are included.